Kedudukan Sumbangan Pihak Ketiga terhadap Keuangan Daerah Propinsi Lampung - Yulia Neta M (Law Faculty of Universitas Bandar Lampung, 2006)
Pupose of research isÂ to analyze Lampung Pro vince Local Regulation Nomor 4/ 1992 regarding position of contribution revenue from thrid party to province local linancial. Result l this research showed position of contribution reveue from thrid party to local Â financial are as financial stateinÂ sence the revenue enter Lampung province local treasury. The lmplementation have been decided by making memorandumÂ Understanding (MOU), and Then continueb dyÂ making contract Â or other agreement Â or Preliminary contact among paties, finalized by Docision of Lampung Goversor.After than contributors directly deposit the contributions toÂ province Treasury,Â in this case isÂ Appointee Bank.